The Influence of Liquidity and Profitability on Firm Value in the Basic Materials Sector with Corporate Social Responsibility (CSR) as a Moderating Variable - Kadek Ary Asta Pramita Sari; Ni Made Suci; Fridayana Yudiatmaja (Dinasti Publisher, 2025)
This study aims to examine the influence of liquidity and profitability on firm value with Corporate Social Responsibility (CSR) as a moderating variable in the basic materials sub-sector. The research employs a quantitative approach using panel data, which combines cross-sectional and time series data. The data used in this study were obtained from companies in the basic materials sector listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. The research population includes all companies in the basic materials sector listed on the IDX, with a purposive sampling technique applied, resulting in 46 companies that met the criteria, totaling 138 samples over the research period. Data were collected through the official IDX website and the financial reports published by the companies. The analysis was conducted using multiple regression with the Moderated Regression Analysis (MRA) method, following the classical assumption tests, such as the Normality Test, Multicollinearity Test, and Heteroscedasticity Test, processed using SPSS software. The results show that liquidity has no significant effect on firm value, while profitability has a positive effect on firm value. Furthermore, CSR is proven to moderate the influence of both liquidity and profitability on firm value with significant effects. This study provides insight into the important role of CSR in moderating the relationship between financial variables and firm value in the basic materials sector.